MORPHOLOGICAL FEATURES OF FRUITS AND ANTIOXIDANT ACTIVITY OF DIFFERENT FORMS OF ROSA ALBERTI UNDER THE CONDITIONS OF THE MAIN BOTANICAL GARDEN (Experimental biology, 2026)
The article presents the results of a study on the morphological characteristics and antioxidant activity of various forms of Albert’s rosehip (Rosa alberti Regel.) introduced and cultivated at the Main Botanical Garden of Kazakhstan. The relevance of the research is determined by growing interest in introducing promising ornamental and medicinally valuable plant species capable of adapting to the continental climate, as well as by the need to expand sources of biologically active compounds. Rosa alberti is notable for its high ornamental value, ecological plasticity, and potential pharmacological significance.The aim of the study was to identify diagnostically significant morphological traits of different Rosa alberti forms and assess the antioxidant potential of the fruits as an indicator of plant adaptation to local microecological conditions.
Keywords: Rosa alberti, morphological traits, antioxidant activity, phenolic compounds, adaptive potential